2008
DOI: 10.1038/cgt.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 amplicon viral vector-mediated gene transfer to human bone marrow-derived mesenchymal stem cells

Abstract: Human bone marrow-derived mesenchymal stem cells (BM-hMSCs) are nonhematopoietic stem cells that have the potential to differentiate into adipocytes, osteocytes and chondrocytes. Because of its propensity to migrate to the sites of injury and the ability to expand them rapidly, BM-hMSCs have been exploited as potential gene transfer vehicles to deliver therapeutic genes. Herein, we evaluated the feasibility of employing herpes simplex virus type I (HSV-1) amplicon viral vector as a gene delivery vector to BM-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…A confluent monolayer culture was observed 7-10 days following initial plating. MSC were then characterized based on the presence of cellular markers CD13, CD44, CD73, CD90, and CD105, as well as its ability to differentiate to osteogenic and adipogenic lineage as previously described [25].…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…A confluent monolayer culture was observed 7-10 days following initial plating. MSC were then characterized based on the presence of cellular markers CD13, CD44, CD73, CD90, and CD105, as well as its ability to differentiate to osteogenic and adipogenic lineage as previously described [25].…”
Section: Cell Culturementioning
confidence: 99%
“…DGli36 cells (kindly provided by Dr. M. Esteves, University of Massachusetts) and 2-2 cells (kindly provided by Dr. R. SandriGoldin, University of California Los Angeles) were cultured as previously described [25]. Human glioma cell line, U87MG, was purchased from American Type Culture Collection (Rockville, MD) and was cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS; Invitrogen, Grand Island, NY).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, infection with helper-free amplicons did not alter the intrinsic properties of these cells, including morphology, proliferation and chromosomal stability. Most important, amplicon infection did not alter the pluripotent differentiation potential and the tumor tropism of BM-hMSCs, 25 nor integrate into cellular chromosomes, therefore avoiding any genotoxic effect. Although the efficiency of migration of BM-hMSCs to the sites of injury has been reported to be low, this study illustrates a potentially very useful application of HSV-1-based amplicon vectors.…”
Section: Transduction Of Progenitor Cells Using Amplicon Vectorsmentioning
confidence: 98%
“…Earlier studies had shown that amplicons expressing FGF-2 efficiently promoted neuron generation on delivery into mouse embryonic stem cells. 24 In a very interesting recent study, Lam and coworkers 25 used amplicon vectors to deliver GFP to human bonemarrow-derived mesenchymal stem cells (BM-hMSCs), non-hematopoietic stem cells that have the potential to differentiate into adipocytes, osteocytes and chondrocytes. As these cells can migrate to sites of injury, where they expand rapidly, BM-hMSCs can be exploited as gene transfer vehicles to deliver therapeutic genes.…”
Section: Transduction Of Progenitor Cells Using Amplicon Vectorsmentioning
confidence: 99%